Analysis of the Impact of Poverty, Human Development Index, and Labor on Domestic Products in the District/City of Bengkulu Province 2017-2021 - Ditra Deviasari; Bambang Agoes Hermanto (Fakultas Ekonomi Dan Bisnis, Universitas Bengkulu, 2023)
This study aims to determine the impact on regional gross domestic product in the districts or cities of Bengkulu province. In data analysis, a panel data regression model was used (combining time series and cross series) for the period 2017–2021 in 10 districts and towns in Bengkulu using Eviews 12. Research results This shows that poverty has a negative and insignificant impact. impact on GRDP; the human development index shows that HDI has a positive and significant impact on GRDP; and dynamic populations have a positive and significant influence on GRDP.